Penilaian Peforma keuangan Bank Syariah dengan Dupont Method (Studi BSM 2016-2020) - Ghoni, Muhammad Abdul (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
In this article the method used to determine the financial performance of PT. Bank Syariah Mandiri is the Du Pont Method. Wich uses three ratios, namely Total Assets Turnover (TATO), Net Profit Margin (NPM), and Return On Investment (ROI). This study focuses on analyzing the financial performance of Bank Syariah Mandiri for the 2016-2020 period and looking at the comparison of financial performance of Bank Syariah Mandiri in the last 5 years. This study uses a quantitative descriptive approach, which describes the numerical data analysis results using quantitative analysis techniques. The following conclusions can be drawn: The highest Return On Investment occurred in 2019 at 1.140% and the lowest occurred in 2016 at 0.413%. In 2019 Return On Investment was above average, this shows that the company's performance in generating profits in that year was very good. The calculation of Return On Investment (ROI) from 2016 - 2020 shows that ROI is still fluctuating and less stable. This illustrates that the BSM merger decision in 2021 is the right decision when viewed from the financial performance.